2004
DOI: 10.1111/j.1949-8594.2004.tb18236.x
|View full text |Cite
|
Sign up to set email alerts
|

Describing and Evaluating an Exemplary Mathematics Elementary Staff Development Project

Abstract: The purpose of this paper is to describe the model of a mathematics and science staff development cooperative and focus on the evaluation of the mathematics component. The Mathematics and Science Education Cooperative (MSEC) was a comprehensive, long‐range staff development program to improve the teaching and learning of mathematics and science at the elementary school level. The special features of MSEC were (a) it provided year‐round, multiyear involvement, and (b) each year an affective strand was included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Some mathematics and science program evaluations have examined teachers' change in instructional practices. For example, Mittag, Shoho, and Lien (2004) reported that teachers in the Mathematics and Science Education Cooperative (MSEC) produced teachers who were “found to be more constructivists in nature. In contrast to the traditional drill and skill approach, elementary students were exposed to more hands‐on and interactive teaching approaches” (p. 151).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some mathematics and science program evaluations have examined teachers' change in instructional practices. For example, Mittag, Shoho, and Lien (2004) reported that teachers in the Mathematics and Science Education Cooperative (MSEC) produced teachers who were “found to be more constructivists in nature. In contrast to the traditional drill and skill approach, elementary students were exposed to more hands‐on and interactive teaching approaches” (p. 151).…”
Section: Literature Reviewmentioning
confidence: 99%